Haematology and Serum Biochemical Indices of Lambs Supplemented with Moringa oleifera, Jatropha curcas and Aloe vera Leaf Extract as Anti-Methanogenic Additives - Abiodun Mayowa Akanmu; Abubeker Hassen; Festus Adeyemi Adejoro (MDPI AG, 2020)
Medicinal plants have been found to be effective in a wide range of applications in ruminant animals. However, some plant extracts may be toxic to animals, depending on their seconday metabolite composition and dose, and therefore, animal trials are needed to validate their safety when used as anti-methanogenic additives. This study investigated the effect of three plant extracts used as anti-methanogenic dietary additives, on the haematology and serum biochemical parameters in sheep. Methanolic extracts of Moringa oleifera (MO), Jatropha curcas (JC) and Aloe vera (AV) were orally dosed as experimental treatments for 75 days to sheep, and their effect on the haematology and serum biochemical parameters of SA Mutton Merino (SAMM) lambs were compared with sheep on a control treatment without any additive treatment. Extracts of MO, JC and AV were extracted in 100% methanol, freeze-dried, and reconstituted in distilled water. A total of 40 lambs were ranked according to their body weight into a group of four and one sheep at a time was randomly allocated into four dietary treatments which include a control treatment, and treatment with either MO, JC or AV extract. Lambs were drenched twice daily with doses equivalent to 50 mg/kg dry matter intake (DMI) based on previous week feed consumption. Blood samples were collected via jugular vein puncture and analysed for haematology and serum biochemistry parameters, using standard procedures. The results of the haematological analysis showed that most haematological parameters were not affected by plant extract used as anti-methanogenic additives (p > 0.05), except for higher white blood cell (WBC) and lymphocytes counts recorded in control lambs and lambs in the AV treatment. All serum biochemical properties (except alkaline phosphatase) were not different (p > 0.05) between the control and lambs treated with plant extracts. Alkaline phosphatase was influenced by the plant extract (p < 0.05), with lambs receiving MO, JC and AV having lower alkaline phosphatase concentrations compared to lambs on the control diet without any additive. The result of the study showed that extracts of MO, JC and AV were not toxic to sheep when used as antimethanogenic additives at the recommended dose of 50 mg/kg dry matter feed which had proved previously to be effective in reducing enteric methane emission. Therefore, these plant extracts could be used safely as alternative dietary additives to reduce enteric methane emission and boost the productivity of SA Mutton Merino sheep.